SOCIENTIZE participatory experiments, dissemination and networking activities in perspective (Human Computation, 2014)
Citizen science includes a wide range of activities in which citizens are involved in research projects, either by collecting or analyzing massive data sets, or by developing small-scale activities, such as grassroots groups taking part in local policy debates. In parallel, the concept of digital society is emerging and triggering a social and information revolution. Here, large scientific infrastructures and high performance communication technologies have resulted in e-science and allow addressing problems that were unsolvable until a few decades ago. Similarly, the millions of people around the world that are permanently interconnected can be considered as a citizen-based infrastructure (c-infrastructure) which can be used for distributed computing, collective talent or ubiquitous data gathering. As a result, we have a complex entity with intelligence and collective knowledge.Funded by the European Commission, SOCIENTIZE is a FP7 project, which aims to set the basis of citizen science in Europe for Horizon2020. For the last two years, SOCIENTIZE has been promoting Citizen Science in order to 1) raise awareness about the importance and impact of citizen science, 2) to foster interaction and coordination between all citizen-science actors, 3) to promote the capabilities of c-infrastructures among researchers and citizens for an enhanced science, 4) to coordinate and promote citizen science projects and finally (5) to collect and share the best practices and recommendations for the implementation of citizen science projects in Europe. To achieve these goals, SOCIENTIZE has developed and implemented several activities that are described in this paper.